ABT-126 monotherapy in mild-to-moderate Alzheimer's dementia: randomized double-blind, placebo and active controlled adaptive trial and open-label extension. Issue 1 (December 2016) - Gault, Laura; Lenz, Robert; Ritchie, Craig; Meier, Andreas; Othman, Ahmed; Tang, Qi; Berry, Scott; Pritchett, Yili; Robieson, Weining
Abstract Background Results from a phase 2a study indicated that treatment with the novel α7 nicotinic acetylcholine receptor agonist ABT-126 25 mg once daily (QD) was associated with a trend for improvement in cognition in subjects with mild-to-moderate Alzheimer's dementia (AD). A phase 2b program was designed to evaluate a broader dose range of ABT-126 as monotherapy in subjects with mild-to-moderate AD. The program consisted of a double-blind, placebo and active controlled study of ABT-126 (dose range 25–75 mg) and an open-label extension study (75 mg). Methods The randomized double-blind study enrolled 438 subjects (Mini-Mental Status Examination score of 10–24, inclusive) not currently taking acetylcholinesterase inhibitors or memantine. Subjects received 24 weeks of ABT-126 25 mg QD (n = 77), ABT-126 50 mg QD (n = 108), ABT-126 75 mg QD (n = 73), donepezil 10 mg QD (n = 76), or placebo (n = 104). The primary endpoint was the change from baseline to week 24 in the 11-item Alzheimer's Disease Assessment Scale—Cognitive subscale (ADAS-Cog) total score. Subjects completing the double-blind study could enroll in the 28-week open-label extension study. Adverse events (AEs) and other safety parameters were monitored in both studies. Results A total of 367 patients (83.8 %) completed the double-blind study and 349 (79.7 %) entered the open-label study. Compared with placebo, donepezil significantly improved ADAS-Cog 11-item total scores from baseline to week 24 (−2.29 ± 0.95; one-sidedP = 0.008). No ABT-126 dose demonstrated a statistically significant improvement vs placebo at week 24 in the ADAS-Cog total score: ABT-126 25 mg, −0.47 ± 0.94 (P = 0.309); ABT-126 50 mg, −0.87 ± 0.85 (P = 0.153); and ABT-126 75 mg, −1.08 ± 0.94 (P = 0.127). Rates of serious AEs and discontinuations due to AEs were similar across treatment groups. The most frequently reported AEs in both studies were constipation, fall, and headache. No clinically meaningful changes were observed in other parameters. Conclusions In the double-blind trial, donepezil significantly improved ADAS-Cog scores but no statistically significant improvement was seen with any ABT-126 dose. ABT-126 had an acceptable safety profile in subjects with mild-to-moderate AD in both studies. Trial registration ClinicalTrials.govNCT01527916, Registered 3 February 2012 (randomized trial). ClinicalTrials.govNCT01676935 . Registered 29 August 2012 (open-label extension study).